A review on antifungal constituents in paddy (Oryza sativa L.) against fungal diseases / Wan Fazlizan Wan Abdullah Sani - Wan Abdullah Sani, Wan Fazlizan (Faculty of Plantation and Agrotechnology, 2016)
Rice or paddy plants (Oryza spp.) produce secondary metabolic as a defense. The previous researchs has been done to identify the antifungal activity as their reaction toward several fungal pathogens attack in the field by Magnaporthe grisea that cause rice blast disease. The plants were extracted the constituents of antifungal in different part of paddy plants to identify their activities toward selected fungus. Those extract then being tested on fungal Pyricularia oryza and Rhizoctonia solani. Extractions from paddy part such as leaves, stem, seed, husk and straw that contains allelochemical as the result. Reaction of compound extraction of antifungal from paddy part against fungal spore were obtain when the result of extraction inhibit the fungal spore germination are shown.